2019
DOI: 10.21037/atm.2018.10.67
|View full text |Cite
|
Sign up to set email alerts
|

Determination of copper poisoning in Wilson’s disease using laser ablation inductively coupled plasma mass spectrometry

Abstract: Copper (Cu) is an essential trace element that is vital to the health of all living organisms. As a transition metal, it is involved in a myriad of biological processes. Balance studies estimated that the adult human requirement for copper is in the range of 1.3 to 2 mg per day. Cu deficiency alters immune function, neuropeptide synthesis and antioxidant defense, while the excess in Cu results in oxidative stress and progressive structural damage of mitochondrial and clinically in hepatic and/or neurological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Recently, we established novel LA-ICP-MS-based protocols for metal bio-imaging in different organs including liver, kidney, and brain [ 19 , 20 ]. We have already comprehensively demonstrated that respective protocols are highly suitable to identify and quantify copper deposits in experimental and clinical samples of WD [ 6 , 7 , 21 , 22 , 23 ]. This technique provides quantitative information about major, minor, and trace elements with wide element coverage and excellent limits of detection [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we established novel LA-ICP-MS-based protocols for metal bio-imaging in different organs including liver, kidney, and brain [ 19 , 20 ]. We have already comprehensively demonstrated that respective protocols are highly suitable to identify and quantify copper deposits in experimental and clinical samples of WD [ 6 , 7 , 21 , 22 , 23 ]. This technique provides quantitative information about major, minor, and trace elements with wide element coverage and excellent limits of detection [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another inherited disorder reflecting the importance of autophagy in liver homeostasis is Wilson’s disease, also known as hepatolenticular degeneration or “copper storage disease”. It represents a rare autosomal recessive disorder caused by mutation in the ATPase copper transporting protein ATP7B, preventing the body from removing excess copper and leading to accumulation of this trace metal in liver and brain [27]. Recently, it was shown that ATP7B-deficient cells showed significant increased expression of autophagy-associated genes when compared to control cells.…”
Section: Autophagy In Homeostasis Of the Liver—implications For Hementioning
confidence: 99%
“…3) enables easy adaptation to special requirements and simple transfer to other systems. Its simplicity further facilitates the quick generation of high-resolution images that can be exported to several common image formats (JPEG, TIFF), which can be depicted in different pseudo-color scales [2432]. ELAI has an overall simple workflow in data analysis and contains special functions and features for calibration, de-spiking, and image export.…”
Section: Elaimentioning
confidence: 99%